Interdisciplinary insights on interpersonal relationships: edited by Xiaoming Jiang, London, United Kingdom, IntechOpen, 2023, Pages 74, ISBN 978-1-80355-631-4, http://doi.org/10.5772/intechopen.98105. - Sulistiawan, Hendra; Firmansyah, Haris; Januardi, Arif (British Journal of Guidance & Counselling, 2026)
This book focuses on the wise and strategic development of interpersonal relationships within dyads, such as teacher-student, parent-child, and business partners, emphasizing the challenges and opportunities in diverse, AI-integrated societies. It explores key themes including the dyadic approach to studying relationships, the role of nonverbal and nonviolent communication, and the use of narrative writing to address social and behavioral issues in educational settings. The book also examines how personality traits and core human values influence friendship quality and highlights mindfulness-based education rooted in Buddhist principles to foster children’s character development. Overall, it offers interdisciplinary insights into managing interpersonal relationships thoughtfully amid contemporary social complexities.